PENDAFTARAN HAK TANGGUNGAN MENURUT UNDANG-UNDANG NOMOR 4 TAHUN 1996 - Marindowati Marindowati (Fiat Justisia: Jurnal Ilmu Hukum, 2007)
To obtain credit, one form of guarantee is a guarantee of security rights stipulated in Law No. 4 of 1996 on Mortgage. A security interest is a security interest that is charged on land rights as defined in the BAL, following or not following other objects which constitute one unit with the ground In order to have legal certainty, then a security interest must be registered. Keywords : Lending, Mortgage.